Polyamine Modulation of Anticonvulsant Drug Response: A Potential Mechanism Contributing to Pharmacoresistance in Chronic Epilepsy - Beckonert, Niklas Michael (J Neurosci, 2018)
Despite the development of numerous novel anticonvulsant drugs, ∼30% of epilepsy patients remain refractory to antiepileptic drugs (AEDs). Many established and novel AEDs reduce hyperexcitability via voltage- and use-dependent inhibition of voltage-gated Na(+) channels. For the widely used anticonvulsant carbamazepine (CBZ), use-dependent block of Na(+) channels is significantly reduced both in experimental and human epilepsy. However, the molecular underpinnings of this potential cellular mechanism for pharmacoresistance have remained enigmatic. Here, we describe the mechanism that leads to the emergence of CBZ-resistant Na(+) channels. We focused on the endogenous polyamine system, which powerfully modulates Na(+) channels in a use-dependent manner. We had shown previously that the intracellular polyamine spermine is reduced in chronic epilepsy, resulting in increased persistent Na(+) currents. Because spermine and CBZ both bind use-dependently in spatial proximity within the Na(+) channel pore, we hypothesized that spermine loss might also be related to diminished CBZ response. Using the pilocarpine model of refractory epilepsy in male rats and whole-cell patch-clamp recordings, we first replicated the reduction of use-dependent block by CBZ in chronically epileptic animals. We then substituted intracellular spermine via the patch pipette in different concentrations. Under these conditions, we found that exogenous spermine significantly rescues use-dependent block of Na(+) channels by CBZ. These findings indicate that an unexpected modulatory mechanism, depletion of intracellular polyamines, leads both to increased persistent Na(+) currents and to diminished CBZ sensitivity of Na(+) channels. These findings could lead to novel strategies for overcoming pharmacoresistant epilepsy that target the polyamine system. SIGNIFICANCE STATEMENT Pharmacoresistant epilepsy affects ∼18 million people worldwide, and intense efforts have therefore been undertaken to uncover the underlying molecular and cellular mechanisms. One of the key known candidate mechanisms of pharmacoresistance has been a loss of use-dependent Na(+) channel block by the anticonvulsant carbamazepine (CBZ), both in human and experimental epilepsies. Despite intense scrutiny, the molecular mechanisms underlying this phenomenon have not been elucidated. We now show that a loss of intracellular spermine in chronic epilepsy is a major causative factor leading to the development of CBZ-resistant Na(+) currents. This finding can be exploited both for the screening of anticonvulsants in expression systems, and for novel strategies to overcome pharmacoresistance that target the polyamine system.